Value of river restoration when living near and far. The Atoyac Basin in Puebla, Mexico / Valor de la restauración de ríos cuando se vive cerca y lejos. La Cuenca de Atoyac en Puebla, México - Soto Montes de Oca, Gloria; Ramírez Fuentes, Alfredo (Tecnología y ciencias del agua, 2019)
On analysing data from a Contingent Valuation (CV) survey to restore the Atoyac River Basin in Puebla, Mexico, we found that households obtain differentiated benefits due to their condition of closeness to or distance from the river, which are in turn often associated with conditions of vulnerability to water pollution and poverty. Our approach was to estimate Willingness to Pay (WTP) for restoration of the Atoyac River that crosses the Puebla State, using models for two population groups: those residing nearby and those living farther away. As expected, the bid offered and the household's income are significant determinants of WTP; however, the remainder of the variables change, denoting that poor people are more concerned about river pollution.